Transient Nutrient Deficiencies in Pea: Consequences on Nutrient Uptake, Remobilization, and Seed Quality - Jacques, Cécile; Forest, Marion; Durey, Vincent; Salon, Christophe; Ourry, Alain; Prudent, Marion (Frontiers in Plant Science, 2021)
Legume plants, such as peas, are of significant nutritional interest for both humans and animals. However, plant nutrition and thus, seed composition, depends on soil mineral nutrient availability. Understanding the impact of their deprivation on the plant mineral nutrient content, net uptake, and remobilization is of key importance but remains complex as the elements of the plant ionome are linked in intricate networks, one element deprivation impacting uptake and remobilization of other nutrients. To get a better insight into pea mineral nutrition, the transitory deprivations of 13 mineral nutrients were imposed during the vegetative growth phase. Thereafter, plants were grown under optimal mineral conditions until physiological maturity. Plant nutritional status and seed quality impacts caused by the deprivations were characterized using measurement of mineral nutrient concentration and plant biomass allocation. Our results highlight: (i) the preferential allocation of dry weight and elements to shoots at the expense of the roots under non-limiting conditions, and more particularly to the tendrils in comparison to the other shoot organs, (ii) the positive and/or negative impact of one mineral nutrient deprivation on other elements of the ionome, (iii) four different remobilization strategies for eight mineral nutrients, and (iv) possible strategies to improve seed quality via fine control of fertilization during a period of mineral nutrient deficiency.